Projected Increasing Negative Impact of Extreme Events on Gross Primary Productivity During the 21st Century in CMIP6 Models - Yuhan Gao; Dan Zhu; Zhen Wang; Zinan Lin; Yao Zhang; Kaicun Wang (Earth's Future)
Abstract In the context of increasingly frequent and severe climate extremes, an understanding of the impacts of these events on gross primary production (GPP) and thus on land carbon uptake is crucial. However, research utilizing new model outputs to assess the future trends, characteristics, and driving factors of GPP reduction associated with extreme events remains limited. Here, we use model outputs from Phase Six of the Coupled Model Intercomparison Project (CMIP6) to investigate the spatiotemporal patterns of negative GPP extreme events during the 21st century. We find a notable increase in negative GPP extremes globally under the SSP5‐8.5 scenario. They are characterized by longer durations and larger sizes, despite the smaller number of events. Under the SSP1‐2.6 scenario, while the total negative GPP extremes remain relatively stable, hotspots, including tropical forests, southern China, and boreal forest zones, still experience increases in negative extremes. By attributing these GPP extremes to climate conditions, we identified compound hot and dry conditions, which contributed to over 40% of the negative GPP extremes under both scenarios, as the dominant driver, followed by single‐driver dry conditions. Under SSP5‐8.5, the increasing contribution of compound hot and dry conditions leads to greater GPP reductions through prolonged and intensified negative extreme events. Compared with CMIP5 models, CMIP6 models project an asymmetry of negative and positive GPP extreme events that favors more negative extremes across most regions. Our findings highlight the escalating damage from climate extremes on future ecosystem productivity, emphasizing the urgent need for effective mitigation and adaptation actions.